Team handball, unpredictability scenario and the methods of teaching-learning-training - Rafael Pombo Menezes; Heloisa Helena Baldy dos Reis; Márcio Pereira Morato (Federación Extremeña de Balonmano; University of Extremadura, 2016)
Team handball present situations that challenge players perception and decision making, especially in the changes that may occur in the games situations. The unpredictability is crucial in these changes by the simultaneity of the random behavior of the players, influenced by factors such as teaching method, the previous experiences and the perception of the player in the game situation. The teaching methods of team sports should encourage those players to adapt their technical and tactical behavior to sudden changes in game situations, not only the development of motor skills out of the game context.